Gendered citizenship : the original conflict over the Equal Rights amendment, 1920-1963 - DeWolf, Rebecca (University of Nebraska Press, 2021)
"Gendered Citizenship outlines how the original conflict over the Equal Rights Amendment (ERA) altered the nature of American Citizenship, creating justification for sex-specific treatment and rights that still exist today"--